Assessing the feasibility of Nipah vaccine efficacy trials based on previous outbreaks in Bangladesh. Issue 39 (15th September 2021) - Nikolay, Birgit; Ribeiro dos Santos, Gabriel; Lipsitch, Marc; Rahman, Mahmudur; Luby, Stephen P.; Salje, Henrik; Gurley, Emily S.; Cauchemez, Simon
Abstract: Background: Nipah virus (NiV) is an emerging, bat-borne pathogen that can be transmitted from person-to-person. Vaccines are currently being developed for NiV, and studies have been funded to evaluate their safety and immunogenicity. An important unanswered question is whether it will be possible to evaluate the efficacy of vaccine candidates in phase III clinical trials in a context where spillovers from the zoonotic reservoir are infrequent and associated with small outbreaks. The objective of this study was to investigate the feasibility of conducting a phase III vaccine trial in Bangladesh, the only country regularly reporting NiV cases. Methods: We used simulations based on previously observed NiV cases from Bangladesh, an assumed vaccine efficacy of 90% and other NiV vaccine target characteristics, to compare three vaccination study designs: (i) cluster randomized ring vaccination, (ii) cluster randomized mass vaccination, and (iii) an observational case-control study design. Results: The simulations showed that, assuming a ramp-up period of 10 days and a mean hospitalization delay of 4 days, a cluster-randomized ring vaccination trial would require 516 years and over 163, 000 vaccine doses to run a ring vaccination trial under current epidemic conditions. A cluster-randomized mass vaccination trial in the two most affected districts would take 43 years and 1.83 million vaccine doses. An observational case-control design in these two districts would require seven years and 2.5 million vaccine doses. Discussion: Without a change in the epidemiology of NiV, ring vaccination or mass vaccination trials are unlikely to be completed within a reasonable time window. In this light, the remaining options are: (i) not conducting a phase III trial until the epidemiology of NiV changes, (ii) identifying alternative ways to licensure such as observational studies or controlled studies in animals such as in the US Food and Drug Administration's (FDA) Animal Rule.